Media dalam Pendekatan Pemikiran Postmodern atau Dekonstruksi - Winda Kustiawan; Dian Indah Multazam; Tuti Restilia (Peneliti.net, 2023)
The power to restore phenomena or reality as a starting point for change lies in the media sphere. In today's world, the media can sometimes serve as a voice for an ideology in promoting societal change. With postmodernism, cultural identity is no longer in accordance with the logic of modernism, but functions according to the context that develops. Because postmodernism tries to undermine modernism by criticizing the structure that is upright and absolute. This also applies to literary works that grow in response to changes in society. Pluralistic thinking between one writer and another in dealing with a situation or an assessment of new things out of the ordinary cannot be considered wrong but rather as pluralistic thinking, which is a characteristic of postmodernist thinking